Reduced killer cell activity of lymphocytes from patients with asbestosis. - Kubota, M (1985)
Immunological abnormalities in 30 patients with asbestosis were investigated by examining the cytoxicity of natural killer (NK) cells and antibody dependent cellular cytotoxicity by killer (K) cells from peripheral blood lymphocytes; the effects of interferon on NK activity was also examined. Fifteen men and 15 women (mean age 58; range 40-72) with asbestosis but who were free of complications such as tuberculosis, carcinoma, or steroid treatment were the subjects for study. There were nine cases of type 1, 19 cases of type 2, and two cases of type 3 disease as described in the ILO classification of pneumoconiosis. They were all textile workers with a mean duration of 18 years (3-40 years) since first exposure to chrysotile. Controls matched for age and sex were selected from a population without occupational exposure to asbestos. The activity of the NK and K cells in patients with asbestosis was significantly lower than in the control group, but the populations of NK and K cells in the peripheral blood lymphocytes were not significantly different in the two groups. An in vitro experiment showed that the increase in the cytotoxicity of the NK cell after treatment with interferon-alpha was significantly lower in the subjects than in the controls. These results indicate that one of the defence mechanisms in relation to cancer is deficient in patients with asbestosis.